2003
DOI: 10.1136/oem.60.7.468
|View full text |Cite
|
Sign up to set email alerts
|

The effect on ambulatory blood pressure of working under favourably and unfavourably perceived supervisors

Abstract: Aims:To investigate the role played by employees’ perceptions of their supervisors’ interactional styles as a possible source of workplace stress that may be associated with increased morbidity and mortality rates from cardiovascular disorders in workers in the lower strata of organisational hierarchies.Methods:A controlled, quasi-experimental, field study of female healthcare assistants. Allocation to the experimental and control groups was based on participants’ responses to a supervisor interactional style … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 50 publications
3
42
0
2
Order By: Relevance
“…More specifically, our results offer evidence suggesting that there may be a physiological link between the fairness of decision-making procedures and treatment of employees and their health 1 18. Previous studies found that perceived organisational injustice was associated with elevated ambulatory blood pressure30 and quantitative markers of cardiac dysregulation, including reduced heart rate variability and altered systolic arterial pressure variability 31. These mechanisms may also link organisational justice to disease end points.…”
Section: Discussionsupporting
confidence: 57%
“…More specifically, our results offer evidence suggesting that there may be a physiological link between the fairness of decision-making procedures and treatment of employees and their health 1 18. Previous studies found that perceived organisational injustice was associated with elevated ambulatory blood pressure30 and quantitative markers of cardiac dysregulation, including reduced heart rate variability and altered systolic arterial pressure variability 31. These mechanisms may also link organisational justice to disease end points.…”
Section: Discussionsupporting
confidence: 57%
“…24 Perceptions of unfairness have previously been related to health risk factors such as increased psychological distress, 5 17 heightened levels of unfavourable serum lipids, 25 and raised blood pressure. 26 In this study, we found a 30%-50% excess risk of poor health among men with low relational justice after three and six years of follow up. The corresponding figures for women were lower (10%-30%), but the sex difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 50%
“…More recent studies, which we review here, have stronger research designs and provide more valid and reliable evidence that workplace social interactions are consequential for cardiovascular functioning. (Wager, Feldman, & Hussey, 2003) found that average levels of SBP and DBP were lower when the assistants worked for a direct supervisor whom they viewed positively compared to one they viewed negatively. This study reinforces the importance of examining the quality of relationships and not assuming that two people's structural positions within an organization are sufficient for understanding either beneficial or harmful cardiovascular effects.…”
Section: Protective Cardiovascular Effects During and After Workmentioning
confidence: 93%